'Two months of marriage were sufficient to turn my life upside down': early marriage as a form of gender-based violence. Issue 2 (3rd May 2016) - Belhorma, Souad
ABSTRACT: In Morocco, as elsewhere, early marriage of young women and girls below the age of 18 exposes them to different forms of social, sexual, physical, psychological, and financial violence. This article focuses on the experience of Moroccan women married under the age of 18 and proposes an analytical framework to support better understanding of the relationship between early marriage and gender-based violence against women and girls. The article draws on first-hand research, including focus groups, to gain insights into the attitudes and perceptions of young women themselves regarding the impact of early marriage on their lives.